Telemedicine during COVID- 19: features of legal regulation in the field of administrative liability for errors committed by medical institutions - Raissa Orsayeva; Anna Berestova; Varvara Krasilnikova; Anton Timoshin (Egyptian Journal of Forensic Sciences)
Abstract Background Today, telemedicine has become an important tool for providing medical care and facilitating the exchange of information and experience between medical institutions. During the COVID-19 pandemic, the use of telemedicine has increased significantly, but with this rapid implementation, there have been instances of violations of medical protocols. This paper aims to identify the challenges and opportunities for legal regulation regarding administrative liability for errors made by medical institutions during the provision of telemedicine services. These issues are addressed in the context of global efforts to combat the COVID-19 pandemic. Main body The findings of the study suggest that, in the practice of telemedicine, medical errors may result in administrative liability similar to that in traditional settings but with some unique characteristics. These characteristics arise from the technology, various legal regulations, and law enforcement practices. The most common examples of errors committed by medical institutions within the scope of the study subject include violations of medical standards, disregard for patients’ rights, including their right to confidentiality and protection of personal information, insufficient training and education of personnel, and issues with technical support. Conclusion The main challenges in legally qualifying offenses resulting from errors made by medical institutions (or their personnel), as in the case of traditional medicine, are related to establishing the evidence base and conducting a specialized medical examination to determine the fact of an error and/or prove guilt (or innocence).